Advances in Microporous and Mesoporous Materials - Huirache Acuña, Rafael (IntechOpen, 2020)
Nowadays, microporous and mesoporous materials are versatile solids of great interest due to their structures and pore sizes, which allow their application in many areas. Accordingly, with IUPAC, materials with pore sizes smaller than 2 nm are called microporous and with pore sizes between 2 and 50 nm are called mesoporous. The pore size has an important impact on the material properties and affects their applications. In addition, high surface area, and their ability to incorporate functional groups on the framework are of great relevance for commercial and science applications. This book intends to provide readers with a comprehensive overview of recent improvements in the microporous and mesoporous materials field.